Skills for success the personal development planning handbook - Cottrell, Stella (Palgrave study guides, 2003)
With structured, reflective and practical activities, this text seeks to enable students to think creatively and constructively about personal, academic and career goals. Individuals are encouraged to identify what success really means to them and to plan a path towards achieving their aims.